The Effectiveness of Religious Forgiveness Therapy on Reducing Marital Conflicts and Extramarital Behaviors in Married Women Seeking Divorce - Zenali Araghi, Negin; Kahrazei, Farhad; Khaneghahi, Sophia (KMAN Counseling & Psychology Nexus, 2025)
The present study aimed to evaluate the effectiveness of forgiveness therapy based on religious teachings in reducing marital conflicts and extramarital behaviors (infidelity) in married women seeking divorce. The research employed a quasi-experimental design with a control group. The statistical population included married women seeking divorce who attended family counseling centers in District 1 of Tehran. Sampling was conducted using a convenience sampling method. The sample size consisted of 40 married women seeking divorce, randomly assigned to experimental and control groups. Data were collected using the Marital Conflict Questionnaire (Sanaei et al., 2008) and the Attitudes Toward Infidelity Scale (Whatley, 2008). The results demonstrated that forgiveness therapy based on religious teachings significantly reduced marital conflicts and extramarital behaviors in women seeking divorce, with a significant difference observed between the experimental and control groups (p < .01). Additionally, the effect size indicated a strong impact of forgiveness therapy based on religious teachings on reducing marital conflicts and extramarital behaviors. In essence, adherence to forgiveness therapy, particularly when integrated with religious teachings, enables individuals to minimize marital conflicts and tendencies toward extramarital behaviors.